PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP PEMBANGUNAN LABORATORIUM UNP - Elya Ustarinda (Jurnal Edukasi dan Penelitian Matematika, 2022)
Understanding mathematicals concepts is one of the objectives of learn mathematics. However, the reality of the students' understandings of mathematical concepts in class VIII SMP UNP Laboratory Development is still low. One of the causes is learning that does not involve students actively and is still centered on the teacher. Therefore, a research was conducted by applying the student teams achievement divisions (STAD) cooperative learning model to improve students' understanding of mathematical concepts and to see the development of students' understanding of mathematical concepts during the implementation of the student teams achievement divisions type cooperative learning model. quasi-experimental or quasi-experimental research design with Static Group Design. The population is class VIII students of UNP Laboratory Development Middle School for the 2021/2022 academic year which consists of five classes. Sample selection was done by simple random sampling technique, class VIII. A as the experimental class and class VIII. B as control class. The final test data were analyzed using the t test. Data on the development of students' understanding of mathematical concepts were analyzed using quiz averages, quiz percentages and the achievement of indicators for understanding concepts on quizzes. based on the results of the final test hypothesis test with a significant level obtained P - Value = 0.001 , which means reject . Thus, it can be concluded that the understanding of mathematical concepts of students who studies with the cooperative model of student teams achievement divisions is better than students who learning using conventional learning models. Keywords– understandings of mathematicals concepts, Student Teams Achievement Divisions, quasi-experimental